Anode for lithium secondary battery, method for producing anode for lithium secondary battery, and lithium secondary battery including anode

A silicon-based negative electrode with a ceramic layer addresses the volume expansion and uneven lithium distribution issues in lithium secondary batteries, stabilizing the pre-lithiation process and improving performance and safety.

JP2025502226AActive Publication Date: 2025-01-24LG ENERGY SOLUTION LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024541868
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-05-03
Filing Date
2023-04-17
Publication Date
2025-01-24
Estimated Expiration
2043-04-17

AI Technical Summary

Technical Problem

Silicon-based negative electrodes for lithium secondary batteries face issues such as rapid volume expansion during charging and discharging, leading to conductive path disruption and uneven lithium ion distribution, which deteriorates electrode performance and reduces cycle life.

Method used

A silicon-based negative electrode with a ceramic layer of specific thickness and composition is applied to stabilize the pre-lithiation process, reducing contact points between silicon and lithium, and enhancing uniformity and stability.

Benefits of technology

The ceramic layer stabilizes the pre-lithiation process, improving charging and discharging performance, reducing the risk of ignition, and maintaining electrode integrity, thereby enhancing the capacity and cycle life of lithium secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502226000001_ABST
    Figure 2025502226000001_ABST
Patent Text Reader

Abstract

The present invention relates to a negative electrode for a lithium secondary battery, a method for producing the same, and a lithium secondary battery including the same. The negative electrode includes a negative electrode current collector layer, a silicon-based negative electrode active material layer provided on one or both sides of the negative electrode current collector layer, and a ceramic layer provided on the opposite side of the silicon-based negative electrode active material layer that contacts the negative electrode current collector layer, the ceramic layer including a ceramic layer composition or a dried product thereof, the ceramic layer having a thickness of 0.5 μm to 3 μm, the ceramic layer composition including a ceramic and an organic binder, the ceramic being included in an amount of 80 parts by weight to 95 parts by weight and the organic binder being included in an amount of 5 parts by weight to 20 parts by weight, based on 100 parts by weight of the ceramic layer composition.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of the filing date of Korean Patent Application No. 10-2022-0054788, filed with the Korean Intellectual Property Office on May 3, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present application relates to a negative electrode for a lithium secondary battery, a method for producing a negative electrode for a lithium secondary battery, and a lithium secondary battery including the negative electrode. [Background technology]

[0003] The rapid increase in the use of fossil fuels has led to an increased demand for alternative and clean energy, and one of the most actively researched fields in this area is power generation and storage using electrochemical reactions.

[0004] At present, a representative example of an electrochemical element that utilizes such electrochemical energy is a secondary battery, and the range of its use is tending to expand more and more.

[0005] As technological development and demand for mobile devices increases, the demand for secondary batteries as energy sources is rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used. In addition, research into a method for manufacturing a high-density electrode with a higher energy density per unit volume as an electrode for such high-capacity lithium secondary batteries is being actively conducted.

[0006] In general, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material that inserts and removes lithium ions from the positive electrode. Silicon-based particles having a large discharge capacity can be used as the negative electrode active material.

[0007] In particular, in recent years, in response to the demand for high-density energy batteries, active research has been conducted into methods of increasing capacity by using silicon-based compounds such as Si / C and SiOx, which have a capacity 10 times larger than that of graphite-based materials, as negative electrode active materials. However, in the case of silicon-based compounds, which are high-capacity materials, they are materials with a large capacity compared to conventionally used graphite and have excellent capacity characteristics, but their volume expands rapidly during charging, cutting off the conductive path and reducing battery characteristics, resulting in a decrease in capacity from the beginning. In addition, when silicon-based negative electrodes undergo repeated charge and discharge cycles, lithium ions are not uniformly charged in the depth direction of the negative electrode, and reactions proceed on the surface, accelerating surface deterioration, so performance needs to be improved in terms of battery cycles.

[0008] In order to solve the above problems when using silicon-based compounds as negative electrode active materials, various methods are being discussed, such as a method of controlling the driving potential, a method of further coating a thin film on the active material layer, a method of controlling the particle size of the silicon-based compound, and the development of a binder that suppresses the volume expansion of the silicon-based compound to prevent the conductive path from being broken. In addition, research is being conducted to complement the life characteristics of silicon-based negative electrodes by limiting the usage ratio of silicon-based active materials used during initial charging and discharging through a method of pre-lithiating the silicon-based active material layer and providing the role of a reservoir.

[0009] However, in the case of the above method, since it may deteriorate the performance of the battery, there is a limit to its application, and there is still a limit to the commercialization of the manufacture of negative electrode batteries having a high content of silicon-based compounds. In particular, as the ratio of silicon-based active material contained in the silicon-based active material layer increases, pre-lithiation is concentrated on the surface of the negative electrode, and damage is caused to the silicon-based active material on the surface side, and non-uniform pre-lithiation occurs, resulting in problems in improving the life characteristics.

[0010] Therefore, even when silicon-based compounds are used as active materials, research is needed to prevent deterioration of the electrode surface as charge and discharge cycles proceed, improve the uniformity during pre-lithiation, and improve the capacity characteristics and cycle performance of lithium secondary batteries. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] JP 2009-080971 A Summary of the Invention [Problem to be solved by the invention]

[0012] The present application relates to a negative electrode for a lithium secondary battery, which can prevent deterioration of the electrode surface during charge and discharge cycles, which has been a conventional problem, even when a silicon-based active material is used in the negative electrode, and in particular, which can improve the uniformity during pre-lithiation to improve the capacity characteristics and cycle performance of the lithium secondary battery, a method for manufacturing the negative electrode for a lithium secondary battery, and a lithium secondary battery including the negative electrode. [Means for solving the problem]

[0013] One embodiment of the present specification provides a negative electrode for a lithium secondary battery, comprising: a negative electrode current collector layer; a silicon-based negative electrode active material layer provided on one or both sides of the negative electrode current collector layer; and a ceramic layer provided on the opposite side of the silicon-based negative electrode active material layer to the side in contact with the negative electrode current collector layer; wherein the ceramic layer comprises a ceramic layer composition or a dried product thereof, the ceramic layer has a thickness of 0.5 μm or more and 3 μm or less, the ceramic layer composition comprises a ceramic and an organic binder, and the ceramic is contained in an amount of 80 parts by weight or more and 95 parts by weight or less, and the organic binder is contained in an amount of 5 parts by weight or more and 20 parts by weight or less, based on 100 parts by weight of the ceramic layer composition.

[0014] In still another embodiment, there is provided a method for producing a negative electrode for a lithium secondary battery, the method including the steps of: preparing a negative electrode current collector layer; applying a negative electrode active material layer composition to one or both sides of the negative electrode current collector layer to form a negative electrode active material layer; and applying a ceramic layer composition to a side of the negative electrode active material layer opposite to a side in contact with the negative electrode current collector layer to form a ceramic layer; wherein the ceramic layer has a thickness of 0.5 μm to 3 μm, the ceramic layer composition includes a ceramic, an organic binder, and an organic solvent, and the ceramic is included in an amount of 80 parts by weight to 95 parts by weight and the organic binder is included in an amount of 5 parts by weight to 20 parts by weight, based on 100 parts by weight of the ceramic layer composition.

[0015] Finally, there is provided a lithium secondary battery, comprising: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte. Effect of the Invention

[0016] The negative electrode for a lithium secondary battery according to one embodiment of the present invention is characterized by having a silicon-based negative electrode active material layer and a ceramic layer having a specific composition and thickness on the silicon-based negative electrode active material layer. The negative electrode according to the present application has excellent capacity characteristics and excellent fast charging ability by using the silicon-based negative electrode.

[0017] However, although the problem of the volume expansion caused by using a silicon-based negative electrode can be solved by a process such as pre-lithiation, there is a problem of ignition, particularly due to the reaction between silicon and the lithium layer being too fast during the pre-lithiation process. However, the negative electrode for a lithium secondary battery according to the present application uses a silicon-based active material and includes a ceramic layer of a specific thickness and composition on the top of the negative electrode active material layer, which stabilizes the process speed during pre-lithiation, and thus has the characteristic of being able to significantly increase the stability during the pre-lithiation process.

[0018] That is, by reducing the number of contact points between the silicon-based anode and lithium metal, the charge / discharge uniformity of the silicon-based anode can be improved, thereby improving performance.

[0019] In addition, by further providing a ceramic layer on the silicon-based negative electrode active material layer, the ceramic layer formed on the separator can be eliminated or minimized, and the thickness of the separator can be reduced, resulting in excellent process and cost characteristics.

[0020] That is, the negative electrode for a lithium secondary battery according to the present application has the advantages of an electrode using a high content of Si particles as a single layer active material, and is characterized by the introduction of a ceramic layer having a specific thickness and composition to solve the problems of surface deterioration, uniformity during pre-lithiation, and life characteristics, which are disadvantages of the electrode using a single layer active material. [Brief description of the drawings]

[0021] [Figure 1] FIG. 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Before describing the present invention, some terms will first be defined.

[0023] In this specification, when a part is said to "comprise" a certain component, this means that it may further include other components, rather than excluding other components, unless specifically stated to the contrary.

[0024] In this specification, "p to q" means a range of "not less than p and not more than q".

[0025] In this specification, the "specific surface area" is measured by the BET method, and specifically, is calculated from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using a BELSORP-mini II manufactured by BEL Japan Co., Ltd. That is, in this application, the BET specific surface area may mean the specific surface area measured by the above-mentioned measurement method.

[0026] In this specification, "Dn" means particle size distribution, and refers to the particle size at the n% point of the cumulative particle number distribution by particle size. That is, D50 is the particle size (average particle size) at the 50% point of the cumulative particle number distribution by particle size, D90 is the particle size at the 90% point of the cumulative particle number distribution by particle size, and D10 is the particle size at the 10% point of the cumulative particle number distribution by particle size. Meanwhile, the particle size distribution can be measured using the laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), and the difference in the diffraction pattern due to the particle size when the particles pass through a laser beam is measured to calculate the particle size distribution.

[0027] In this specification, when a polymer contains a certain monomer as a monomer unit, it means that the monomer is involved in a polymerization reaction and is contained as a repeating unit in the polymer. In this specification, when a polymer contains a monomer, this is interpreted as the same as when a polymer contains a monomer as a monomer unit.

[0028] In this specification, the term "polymer" is understood to be used in a broad sense including copolymers, unless otherwise specified as a "homopolymer."

[0029] In this specification, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are polystyrene-equivalent molecular weights measured by gel permeation chromatography (GPC) using monodisperse polystyrene polymers (standard samples) of various polymerization degrees that are commercially available for molecular weight measurement as standard substances. In this specification, the molecular weight means the weight average molecular weight unless otherwise specified.

[0030] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings in order to enable those skilled in the art to easily carry out the present invention. However, the present invention may be embodied in many different forms and is not limited to the following description.

[0031] One embodiment of the present specification provides a negative electrode for a lithium secondary battery, comprising: a negative electrode current collector layer; a silicon-based negative electrode active material layer provided on one or both sides of the negative electrode current collector layer; and a ceramic layer provided on the opposite side of the silicon-based negative electrode active material layer to the side in contact with the negative electrode current collector layer; wherein the ceramic layer comprises a ceramic layer composition or a dried product thereof, the ceramic layer has a thickness of 0.5 μm or more and 3 μm or less, the ceramic layer composition comprises a ceramic and an organic binder, and the ceramic is contained in an amount of 80 parts by weight or more and 95 parts by weight or less, and the organic binder is contained in an amount of 5 parts by weight or more and 20 parts by weight or less, based on 100 parts by weight of the ceramic layer composition.

[0032] The negative electrode for a lithium secondary battery according to the present application has the advantages of an electrode using a high content of Si particles as a single-layer active material, and is characterized by the introduction of a ceramic layer having a specific thickness and composition in order to solve the problems of surface deterioration, uniformity during pre-lithiation, and life characteristics, which are disadvantages of the electrode using a single-layer active material.

[0033] 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. Specifically, a negative electrode for a lithium secondary battery 100 including a negative electrode active material layer 20 and a ceramic layer 10 on one side of a negative electrode current collector layer 30 can be seen. Although FIG. 1 shows that the negative electrode active material layer is formed on one side, it may be included on both sides of the negative electrode current collector layer.

[0034] The negative electrode for a lithium secondary battery of the present invention will be described in more detail below.

[0035] The present invention provides a negative electrode for a lithium secondary battery, the negative electrode comprising: a negative electrode current collector layer; a silicon-based negative electrode active material layer provided on one or both sides of the negative electrode current collector layer; and a ceramic layer provided on the surface of the silicon-based negative electrode active material layer opposite to the surface in contact with the negative electrode current collector layer.

[0036] In one embodiment of the present application, the negative electrode current collector layer generally has a thickness of 1 μm to 100 μm. Such a negative electrode current collector layer is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the binding force of the negative electrode active material can be strengthened by forming fine irregularities on the surface, and it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0037] In one embodiment of the present application, the negative electrode current collector layer may have a thickness of 1 μm or more and 100 μm or less.

[0038] However, the thickness may vary depending on the type and application of the negative electrode used, and is not limited thereto.

[0039] In one embodiment of the present application, the silicon-based negative electrode active material layer contains a negative electrode active material layer composition, and the negative electrode active material layer composition includes at least one selected from the group consisting of a silicon-based active material, a negative electrode conductive material, and a negative electrode binder, to provide a negative electrode for a lithium secondary battery.

[0040] In one embodiment of the present application, the silicon-based active material may include at least one selected from the group consisting of SiOx (x = 0), SiOx (0 < x < 2), SiC, and Si alloy.

[0041] In one embodiment of the present application, the silicon-based active material includes at least one selected from the group consisting of SiOx (x = 0), SiOx (0 < x < 2), and metal impurities, and based on 100 parts by weight of the silicon-based active material, the SiOx (x = 0) may be included in an amount of 70 parts by weight or more.

[0042] In another embodiment, the silicon-based active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, the SiOx (x = 0) may be included in an amount of 70 parts by weight or more.

[0043] In another embodiment, based on 100 parts by weight of the silicon-based active material, the SiOx (x = 0) may be included in an amount of 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more, and may be included in an amount of 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less.

[0044] In one embodiment of the present application, as the silicon-based active material, pure silicon (Si) can be particularly used. Using pure silicon (Si) as the silicon-based active material may mean including pure Si particles (SiOx (x = 0)) not combined with other particles or elements within the above range when based on a total of 100 parts by weight of the silicon-based active material as described above.

[0045] In one embodiment of the present application, the silicon-based active material may consist of SiOx (x=0).

[0046] Silicon-based active materials have a significantly higher capacity than conventional graphite-based active materials, and efforts to use them are increasing. However, because of their high volume expansion during charging and discharging, their use is limited to mixing a small amount with graphite-based active materials.

[0047] The negative electrode active material layer according to the present application contains a silicon-based active material, specifically, pure silicon particles containing 70 parts by weight or more of SiOx (x=0). In this case, when the pure silicon particles are contained in a high content, the capacity characteristics are excellent, and in order to solve the characteristic of the shortened life due to the surface non-uniform reaction, the above problem is solved by including the ceramic layer according to the present invention.

[0048] On the other hand, the average particle size (D50) of the silicon-based active material of the present invention may be 5 μm to 10 μm, specifically 5.5 μm to 8 μm, and more specifically 6 μm to 7 μm. If the average particle size is less than 5 μm, the specific surface area of ​​the particles increases excessively, and the viscosity of the negative electrode slurry increases excessively. As a result, the particles constituting the negative electrode slurry are not dispersed smoothly. If the size of the silicon-based active material is too small, the contact area between the silicon particles and the conductive material is reduced due to the complex of the conductive material and the binder in the negative electrode slurry, so that the conductive network is likely to be disconnected, and the capacity retention rate is reduced. On the other hand, if the average particle size exceeds 10 μm, the silicon particles are too large, and the surface of the negative electrode is not smooth, which causes current density nonuniformity during charging and discharging. If the silicon particles are too large, the phase stability of the negative electrode slurry becomes unstable, and the processability is reduced. As a result, the capacity retention rate of the battery is reduced.

[0049] In one embodiment of the present application, the silicon-based active material generally has a characteristic BET specific surface area. The BET specific surface area of ​​the silicon-based active material is preferably less than 0.01 m 2 / g~150.0m 2 / g, more preferably 0.1m 2 / g~100.0m 2 / g, particularly preferably 0.2m 2 / g~80.0m 2 / g, most preferably 0.2m 2 / g~18.0m 2 / g. The BET specific surface area is determined in accordance with DIN 66131 (using nitrogen).

[0050] In one embodiment of the present application, silicon-based active material can be, for example, in crystalline or amorphous form, and is preferably not porous.Silicon particles are preferably spherical or shard particles.Alternatively, but less preferably, silicon particles can have a fibrous structure or be in the form of silicon-containing film or coating.

[0051] In one embodiment of the present application, the negative electrode composition includes 70 parts by weight or more of the silicon-based active material based on 100 parts by weight of the negative electrode active material layer composition.

[0052] In another embodiment, the silicon-based active material may be included in an amount of 70 parts by weight or more, preferably 75 parts by weight or more, and more preferably 80 parts by weight or more, based on 100 parts by weight of the negative electrode composition, and may be included in an amount of 95 parts by weight or less, preferably 90 parts by weight or less, and more preferably 85 parts by weight or less.

[0053] The negative electrode active material layer composition according to the present application uses a silicon-based active material with a remarkably high capacity within the above range, and uses a ceramic layer described below together with the silicon-based active material without lowering the capacity performance of the entire negative electrode, and solves the problems of surface deterioration during charging and discharging, uniformity during pre-lithiation, and life characteristics. In addition, by using a specific conductive material and binder that can suppress the volume expansion rate during charging and discharging, the negative electrode performance is not lowered even if the above range is included, and the composition has excellent output characteristics during charging and discharging.

[0054] In one embodiment of the present application, the silicon-based active material may have a non-spherical morphology, and the sphericity thereof is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.

[0055] In this application, the circularity is determined by the following formula 1, where A is the area and P is the perimeter. [Formula 1] 4πA / P 2

[0056] In the past, it was common to use only graphite-based compounds as negative electrode active materials, but in recent years, as the demand for high-capacity batteries has increased, attempts to mix and use silicon-based active materials to increase capacity have been increasing. However, in the case of silicon-based active materials, even if the properties of the silicon-based active materials themselves are adjusted as described above, there are some problems in that the volume of the silicon-based active materials rapidly expands during the charge / discharge process, damaging the conductive path formed in the negative electrode active material layer.

[0057] Therefore, in one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the negative electrode active material layer composition comprises at least one selected from the group consisting of a negative electrode conductive material; and a negative electrode binder.

[0058] In one embodiment of the present application, the negative electrode conductive material may include at least one selected from the group consisting of a dot-like conductive material, a sheet-like conductive material, and a linear conductive material.

[0059] In one embodiment of the present application, the dot-shaped conductive material means a spherical or dot-shaped conductive material that can be used to improve the conductivity to the negative electrode and has conductivity without inducing a chemical change. Specifically, the dot-shaped conductive material may be at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, and may preferably include carbon black in that it realizes high conductivity and has excellent dispersibility.

[0060] In one embodiment of the present application, the point-like conductive material has a BET specific surface area of ​​40 m 2 / g or more 70m 2 / g or less, preferably 45m 2 / g or more 65m 2 / g or less, more preferably 50m 2 / g or more 60m 2 / g or less.

[0061] In one embodiment of the present application, the dotted conductive material may have a functional group content (volatile matter) of 0.01% or more and 1% or less, preferably 0.01% or more and 0.3% or less, and more preferably 0.01% or more and 0.1% or less.

[0062] In particular, when the functional group content of the dot-shaped conductive material satisfies the above range, functional groups are present on the surface of the dot-shaped conductive material, and when water is used as a solvent, the dot-shaped conductive material can be smoothly dispersed in the solvent.

[0063] In one embodiment of the present application, the active material is characterized in that it contains a dot-shaped conductive material having a functional group content in the above range together with a silicon-based active material, and the functional group content can be adjusted depending on the degree of heat treatment of the dot-shaped conductive material.

[0064] That is, in the production of the point-like conductive material, a high functional group content can mean that there is a lot of foreign matter, and a low functional group content can mean that more heat treatment processing has been carried out.

[0065] In one embodiment of the present application, the particle diameter of the dotted conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 20 nm to 60 nm.

[0066] In one embodiment of the present application, the negative electrode conductive material may include a sheet conductive material.

[0067] The planar conductive material can improve conductivity by increasing surface contact between silicon particles in the negative electrode, and at the same time, can suppress the disconnection of the conductive path due to volume expansion, and can be expressed as a plate-type conductive material or a bulk-type conductive material.

[0068] In one embodiment of the present application, the sheet conductive material may include at least one selected from the group consisting of platelet graphite, graphene, graphene oxide, and graphite flakes, and may be preferably platelet graphite.

[0069] In one embodiment of the present application, the average particle size (D50) of the sheet conductive material may be 2 μm to 7 μm, specifically 3 μm to 6 μm, and more specifically 4 μm to 5 μm. If the range is satisfied, the sufficient particle size makes it easy to disperse without causing an excessive increase in the viscosity of the negative electrode slurry. Therefore, when dispersing using the same device and time, the dispersion effect is excellent.

[0070] In one embodiment of the present application, the sheet conductive material may have a D10 of 0.5 μm or more and 1.5 μm or less, a D50 of 2.5 μm or more and 3.5 μm or less, and a D90 of 7.0 μm or more and 15.0 μm or less.

[0071] In one embodiment of the present application, the sheet conductive material may be a sheet conductive material having a high BET specific surface area; or a sheet conductive material having a low specific surface area.

[0072] In one embodiment of the present application, the sheet conductive material may be a high-specific surface area sheet conductive material or a low-specific surface area sheet conductive material without any restrictions. However, the sheet conductive material in the present application may be affected to some extent by dispersion in terms of electrode performance, and it may be particularly preferable to use a low-specific surface area sheet conductive material that does not cause dispersion problems.

[0073] In one embodiment of the present application, the sheet conductive material has a BET specific surface area of ​​5 m 2 / g or more.

[0074] In another embodiment, the sheet conductive material has a BET specific surface area of ​​5 m 2 / g or more 500m 2 / g or less, preferably 5m 2 / g or more 300m 2 / g or less, more preferably 5m 2 / g or more 250m 2 / g or less.

[0075] In another embodiment, the sheet conductive material is a high specific surface area sheet conductive material having a BET specific surface area of ​​50 m 2 / g or more 500m 2 / g or less, preferably 80m 2 / g or more 300m 2 / g or less, more preferably 100m 2 / g or more 300m 2 / g or less.

[0076] In another embodiment, the sheet conductive material is a sheet conductive material having a low specific surface area and a BET specific surface area of ​​5 m 2 / g or more 40m 2 / g or less, preferably 5m 2 / g or more 30m 2 / g or less, more preferably 5m 2 / g or more 25m 2 / g or less.

[0077] Other conductive materials may include linear conductive materials such as carbon nanotubes. The carbon nanotubes may be bundled carbon nanotubes. The bundled carbon nanotubes may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle type" refers to a secondary shape in the form of a bundle or rope in which a plurality of carbon nanotube units are arranged in a line with the longitudinal axes of the carbon nanotube units substantially aligned in the same direction or are entangled. The carbon nanotube units have a graphite sheet with a nano-sized diameter and a cylindrical shape with an sp2 bond structure. In this case, the graphite sheet may exhibit conductive or semiconductive properties depending on the angle and structure of the graphite sheet. The bundled carbon nanotubes can be uniformly dispersed during the manufacture of the negative electrode compared to entangled type carbon nanotubes, and can smoothly form a conductive network in the negative electrode, thereby improving the conductivity of the negative electrode.

[0078] In one embodiment of the present application, the linear conductive material may include SWCNTs; or MWCNTs.

[0079] In one embodiment of the present application, there is provided a negative electrode composition in which the negative electrode conductive material is 10 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the negative electrode active material layer composition.

[0080] In another embodiment, the negative electrode conductive material may be included in an amount of 10 parts by weight or more and 40 parts by weight or less, preferably 10 parts by weight or more and 30 parts by weight or less, and more preferably 10 parts by weight or more and 25 parts by weight or less, based on 100 parts by weight of the negative electrode composition.

[0081] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, the negative electrode conductive material comprising a sheet conductive material and a linear conductive material, the sheet conductive material being contained in an amount of 80 parts by weight or more and 99.9 parts by weight or less based on 100 parts by weight of the negative electrode conductive material.

[0082] In another embodiment, the sheet conductive material may be 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, and more preferably 95 parts by weight or more and 99.9 parts by weight or less, based on 100 parts by weight of the negative electrode conductive material.

[0083] In another embodiment, the amount of the linear conductive material may be 0.1 parts by weight or more and 20 parts by weight or less, preferably 0.1 parts by weight or more and 10 parts by weight or less, and more preferably 0.1 parts by weight or more and 5 parts by weight or less, based on 100 parts by weight of the negative electrode conductive material.

[0084] In particular, in one embodiment of the present application, the negative electrode conductive material includes a planar conductive material and a linear conductive material, each of which satisfies the above-mentioned composition and ratio, so that the battery does not have a significant effect on the life characteristics of existing lithium secondary batteries, there are more points at which charging and discharging are possible, and the battery has the characteristic of excellent output characteristics at a high C-rate.

[0085] The negative electrode conductive material according to the present application has a completely different structure from the conductive material applied to the positive electrode. That is, the negative electrode conductive material according to the present application serves to capture the contact between the silicon-based active materials, which have a very large volume expansion of the electrodes due to charging and discharging, while the positive electrode conductive material serves to provide some conductivity while acting as a buffer having a shock-absorbing function when rolled, and has a completely different structure and role from the negative electrode conductive material of the present invention.

[0086] In addition, the negative electrode conductive material according to the present application is applied to a silicon-based active material, and has a completely different structure from a conductive material applied to a graphite-based active material. That is, a conductive material used in an electrode having a graphite-based active material has a property of improving output characteristics and imparting some electrical conductivity simply because it has smaller particles than the active material, and its structure and role are completely different from a negative electrode conductive material applied together with a silicon-based active material as in the present invention.

[0087] In one embodiment of the present application, the planar conductive material used as the negative electrode conductive material has a structure and role different from that of a carbon-based active material generally used as an existing negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material may be artificial graphite or natural graphite, and refers to a material that is processed into a spherical or dot-like shape to facilitate the storage and release of lithium ions.

[0088] Meanwhile, the planar conductive material used as the negative electrode conductive material is a material having a planar or plate-like shape and can be expressed as plate-like graphite. That is, it is a material contained in the negative electrode active material layer to maintain a conductive path, and does not play a role in storing and releasing lithium, but means a material for securing a planar conductive path inside the negative electrode active material layer.

[0089] That is, in the present application, the use of plate-shaped graphite as a conductive material means that it is processed into a planar or plate-shaped form and used as a material to secure a conductive path, rather than to store or release lithium. In this case, the negative electrode active material contained therein has high capacity characteristics for storing and releasing lithium, and plays a role in storing and releasing all the lithium ions transferred from the positive electrode.

[0090] Meanwhile, in the present application, the use of a carbon-based active material as an active material means that the carbon-based active material is processed into a dot-like or spherical shape and is used as a material that serves to store or release lithium.

[0091] That is, in one embodiment of the present application, the carbon-based active material, artificial graphite or natural graphite, is in a dot-like form and has a BET specific surface area of ​​0.1 m 2 / g or more 4.5m 2 / g or less. The plate-shaped graphite, which is a planar conductive material, is planar and has a BET specific surface area of ​​5 m 2 / g or more.

[0092] In one embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and substances in which hydrogen is substituted with Li, Na, Ca, or the like, or may include various copolymers thereof.

[0093] The negative electrode binder according to one embodiment of the present application plays a role in holding down the active material and conductive material to prevent twisting and structural deformation of the negative electrode structure during volume expansion and relaxation of the silicon-based active material. As long as the above role is satisfied, any common binder can be applied, specifically, a water-based binder can be used, and more specifically, a PAM-based binder can be used.

[0094] In one embodiment of the present application, the amount of the negative electrode binder is 30 parts by weight or less, preferably 25 parts by weight or less, and more preferably 20 parts by weight or less, based on 100 parts by weight of the negative electrode composition, and may be 5 parts by weight or more, or 10 parts by weight or more.

[0095] In particular, the negative electrode binder according to the present application uses an aqueous binder in the case of using a silicon-based active material having high rigidity. The aqueous binder is a polymer that exhibits very high rigidity after drying. By including an aqueous binder in the negative electrode active material layer composition according to the present application, when a ceramic layer made of an aqueous system is coated on the top of a silicon-based negative electrode active material layer made of an aqueous system and then dried, the surfaces are mixed with water and inter-mixing occurs no matter how quickly the material is dried. In order to solve the above problem, the ceramic layer according to the present application uses an organic binder and an organic solvent, and is characterized in that the ceramic and organic binder can be easily dispersed without affecting the negative electrode made of an aqueous system, and a very dense coating can be formed on the negative electrode active material layer.

[0096] In one embodiment of the present application, the negative electrode active material layer further includes a ceramic layer provided on a surface of the silicon-based negative electrode active material layer opposite to a surface in contact with the negative electrode current collector layer.

[0097] As described above, the negative electrode for a lithium secondary battery according to the present application includes a ceramic layer, and by including the above-mentioned negative electrode active material, the negative electrode maintains high capacity and high density characteristics, and solves the problems of surface deterioration during charge and discharge, uniformity during pre-lithiation, and life characteristics.

[0098] In one embodiment of the present application, the ceramic layer may comprise a ceramic layer composition or a dried product thereof.

[0099] In this case, "including the ceramic layer composition" may mean that the ceramic layer includes the ceramic layer composition as is, and "including the dried product of the ceramic layer composition" may mean that all of the organic solvent that may be included in the ceramic layer composition is removed after drying and is not included in the ceramic layer.

[0100] In one embodiment of the present application, the ceramic layer may have a thickness of 0.5 μm or more and 3 μm or less.

[0101] In another embodiment, the thickness of the ceramic layer may be in the range of 0.5 μm to 3 μm, preferably 0.7 μm to 2.5 μm.

[0102] As described above, when the thickness of the ceramic layer satisfies the above range, the effect of improving stability by controlling the rate of prelithiation during prelithiation can be obtained. If the thickness of the ceramic layer exceeds the above range, problems such as deterioration of the performance of the negative electrode may occur, and the efficiency during prelithiation may be reduced. Also, if the thickness of the ceramic layer is less than the above range, it is difficult to control the rate of prelithiation, and the electrode may deteriorate due to a surface reaction on the upper part of the negative electrode active material layer, resulting in a shortened lifespan.

[0103] In one embodiment of the present application, the ceramic layer composition may include a ceramic and an organic binder.

[0104] In one embodiment of the present application, the ceramic can be used without limitation as long as it can function as a ceramic layer. Specifically, the ceramic can be Al2O3, ZrO2, SiO2, TiO2, ZnO, BaTiO3, SrTiO3, CaCO3, CaO, CeO2, NiO, MgO, SnO2, Y2O3, Pb(Zr,Ti)O3 (PZT), (Pb,La)(Zr,Ti)O3 (PLZT), PB(Mg3Nb 2 / 3 The present invention provides a negative electrode for a lithium secondary battery, which contains one or more materials selected from the group consisting of PMN-PT, PbTiO3, and hafnia (HfO2).

[0105] More specifically, the ceramic may be Al2O3, or CeO2.

[0106] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the ceramic composition further comprises an organic solvent, and the organic solvent comprises at least one selected from the group consisting of N-methylpyrrolidone (NMP); dimethylformamide (DMF); acetone; and dimethylacetamide.

[0107] More preferably, the organic solvent may be acetone.

[0108] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, in which the organic binder is polyvinylidene fluoride (PVdF); or polyvinylidene fluoride-hexafluoropropylene (PVdF-HFP).

[0109] In particular, as described above, the silicon-based negative active material layer uses an aqueous binder due to the characteristics of the silicon-based active material, and the ceramic layer uses an organic binder and an organic solvent for dispersing the organic binder to ensure the coating properties of the ceramic layer.

[0110] In addition, while aqueous binders are polymers that exhibit very high rigidity after drying, they generally fall into the category of binders whose adhesive strength decreases after drying, whereas organic binders used in ceramic layers are very soft polymers that exhibit a slight amount of stickiness, i.e. adhesive strength, compared to aqueous binders.

[0111] As a result, during pre-lithiation, a lithium metal layer is transferred onto the ceramic layer. In this case, if the ceramic layer contains an organic binder, the lithium metal layer can be easily transferred onto the ceramic layer through the expression of a small amount of adhesive strength as described above, and processability can also be improved.

[0112] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, in which a surface of the ceramic layer opposite to a surface in contact with the negative electrode active material layer is joined to lithium metal, and then the surface is allowed to stand at 23° C. for 10 seconds to 2 minutes, and then an adhesive strength is provided of 10 gf / 15 mm or more and 100 gf / 15 mm or less.

[0113] The adhesive strength was measured at 90° and a speed of 5 mm / s using a peel strength tester with 3M 9070 tape. Specifically, one side of the lithium metal layer of the negative electrode, in which the lithium metal layer is laminated on the top of the ceramic layer, was attached to one side of a slide glass (3M 9070 tape) to which an adhesive film was attached. Then, the adhesive was attached by reciprocating 5 to 10 times with a 2 kg rubber roller, and the adhesive strength (peel strength) was measured at an angle of 90° and a speed of 5 mm / s. The adhesive strength can be measured at 23°C and normal pressure.

[0114] In one embodiment of the present application, normal pressure may mean pressure in a state where no specific pressure is applied or reduced, and may be used in the same sense as atmospheric pressure. Generally, it may be expressed as 1 atmosphere.

[0115] In one embodiment of the present application, the adhesive strength after joining a surface of the ceramic layer opposite to the surface in contact with the negative electrode active material layer to lithium metal and then leaving the surface at 23° C. for 10 seconds to 2 minutes may be 10 gf / 15 mm or more and 100 gf / 15 mm or less, preferably 15 gf / 15 mm or more and 95 gf / 15 mm or less, and more preferably 20 gf / 15 mm or more and 50 gf / 15 mm or less.

[0116] As described above, when the adhesive strength between the ceramic layer and the lithium metal satisfies the above range, the adhesive strength between the lithium metal and the ceramic layer is good, and transferability is ensured when the lithium metal is transferred using the transfer process of the pre-lithiation process, and problems such as reverse transfer do not occur, allowing the pre-lithiation process to proceed smoothly.

[0117] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the ceramic is contained in an amount of 80 parts by weight or more and 95 parts by weight or less, and the organic binder is contained in an amount of 5 parts by weight or more and 20 parts by weight or less, based on 100 parts by weight of the ceramic layer composition.

[0118] In this case, since the organic solvent that may be contained in the ceramic layer composition does not correspond to an effective substance, the basis of 100 parts by weight of the ceramic layer composition may mean the parts by weight including only the ceramic and the organic binder.

[0119] In one embodiment of the present application, the ceramic may be present in an amount of 80 parts by weight or more and 95 parts by weight or less, preferably 85 parts by weight or more and 95 parts by weight or less, and more preferably 90 parts by weight or more and 95 parts by weight or less, based on 100 parts by weight of the ceramic layer composition.

[0120] In one embodiment of the present application, the organic binder may be present in an amount of 5 parts by weight or more and 20 parts by weight or less, preferably 5 parts by weight or more and 15 parts by weight or less, and more preferably 5 parts by weight or more and 10 parts by weight or less, based on 100 parts by weight of the ceramic layer composition.

[0121] As described above, since the ceramic layer composition contains the organic binder and ceramic in the above-mentioned amounts, the dispersibility of the binder and ceramic is improved, and the ceramic layer is uniformly formed, so that the prelithiation rate can be smoothly controlled, and the coating density during coating of the ceramic layer can be improved by satisfying an appropriate viscosity range.

[0122] In one embodiment of the present application, the negative electrode active material layer may have a thickness of 10 μm or more and 200 μm or less.

[0123] In one embodiment of the present application, the negative electrode for a lithium secondary battery may be a pre-lithiated negative electrode.

[0124] In one embodiment of the present application, there is provided a method for producing a negative electrode for a lithium secondary battery, the method including the steps of: preparing a negative electrode current collector layer; applying a negative electrode active material layer composition to one or both sides of the negative electrode current collector layer to form a negative electrode active material layer; and applying a ceramic layer composition to a side of the negative electrode active material layer opposite to a side in contact with the negative electrode current collector layer to form a ceramic layer; wherein the ceramic layer has a thickness of 0.5 μm or more and 3 μm or less, the ceramic layer composition includes a ceramic, an organic binder, and an organic solvent, and the ceramic is included in an amount of 80 parts by weight or more and 95 parts by weight or less and the organic binder is included in an amount of 5 parts by weight or more and 20 parts by weight or less, based on 100 parts by weight of the ceramic layer composition.

[0125] In the method for producing the negative electrode, the compositions and contents included in each step may be the same as those described above.

[0126] In one embodiment of the present application, a negative electrode active material layer composition is applied to one or both surfaces of the negative electrode current collector layer to form a negative electrode active material layer.

[0127] That is, the step is a step of forming a negative electrode active material layer on a negative electrode current collector layer, and may refer to a step of forming an active material layer on a surface in contact with the current collector layer.

[0128] In one embodiment of the present application, applying the negative electrode active material layer composition includes applying and drying a negative electrode slurry including the negative electrode active material layer composition; and a negative electrode slurry solvent.

[0129] At this time, the solid content of the negative electrode slurry may be in the range of 10% to 40%.

[0130] In one embodiment of the present application, the step of forming the negative electrode active material layer may include the steps of mixing the negative electrode slurry; and coating one or both sides of the negative electrode current collector layer with the mixed negative electrode slurry, and the coating may be performed using a coating method commonly used in the art.

[0131] Thereafter, in one embodiment of the present application, a step of forming a ceramic layer by applying a ceramic layer composition to a surface of the negative active material layer opposite to a surface in contact with the negative current collector layer is provided.

[0132] In one embodiment of the present application, there is provided a method for producing a negative electrode for a lithium secondary battery, comprising the steps of applying the ceramic layer composition, and then drying and rolling the applied ceramic layer composition to remove an organic solvent from the ceramic layer composition.

[0133] In one embodiment of the present application, the negative electrode slurry solvent may be used without limitation as long as it can dissolve and disperse the negative electrode active material layer composition, and specifically, water or NMP may be used.

[0134] In one embodiment of the present application, there is provided a method for manufacturing a negative electrode for a lithium secondary battery, the method including a step of pre-lithiating a negative electrode in which a negative electrode active material layer and a ceramic layer are formed on the negative electrode current collector, the step of pre-lithiating the negative electrode including a lithium electrolytic plating process; a lithium metal transfer process; a lithium metal deposition process; or a stabilized lithium metal powder (SLMP) coating process.

[0135] The negative electrode for a lithium secondary battery as described above includes SiOx (x=0) for enhancing capacity characteristics as a negative electrode active material layer, and the ceramic layer has the above-mentioned specific composition and thickness, so that it can have the advantage of fast charging. That is, compared to the case where only a negative electrode active material layer is applied, the ceramic layer has the above-mentioned composition, so that a uniform pre-lithiation process can be performed at the upper end of the negative electrode, and thus the life span can be further improved.

[0136] In one embodiment of the present application, the porosity of the negative electrode active material layer may be in the range of 10% or more and 60% or less.

[0137] In another embodiment, the porosity of the negative electrode active material layer may be in the range of 10% or more and 60% or less, preferably 20% or more and 50% or less, and more preferably 30% or more and 45% or less.

[0138] The porosity varies depending on the composition and content of the silicon-based active material, the negative electrode conductive material, and the negative electrode binder contained in the negative electrode active material layer, and is characterized by having an appropriate range of electrical conductivity and resistance in the electrode.

[0139] In one embodiment of the present application, there is provided a lithium secondary battery including: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte.

[0140] A secondary battery according to an embodiment of the present specification may include the negative electrode for a lithium secondary battery described above. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the negative electrode described above. The negative electrode has been described above, so a detailed description thereof will be omitted.

[0141] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.

[0142] In the positive electrode, the positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can usually have a thickness of 3 μm to 500 μm, and fine irregularities can be formed on the surface of the current collector to increase the adhesive force of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0143] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-c2 M c2 Lithium nickel oxide with Ni site represented by the chemical formula LiMnO2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≦c2≦0.3); 2-c3 M c3 Examples of the lithium manganese composite oxide include, but are not limited to, lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01≦c3≦0.1) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu, and Zn); and LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion. The positive electrode may be Li metal.

[0144] The positive electrode active material layer may contain a positive electrode conductive material and a positive electrode binder in addition to the above-mentioned positive electrode active material.

[0145] At this time, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed.Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in mixture.

[0146] The positive electrode binder plays a role in improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination.

[0147] The separator separates the negative electrode and the positive electrode and provides a passage for lithium ions to move. Any separator that is generally used in secondary batteries can be used without any particular restrictions. In particular, it is preferable that the separator has low resistance to the ion movement of the electrolyte and excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, a coated separator containing a ceramic component or a polymeric substance may be used to ensure heat resistance or mechanical strength, and may be used selectively in a single layer or multilayer structure.

[0148] In particular, by having a ceramic layer on the silicon-based negative electrode active material layer according to the present application, the ceramic layer formed on the separator can be eliminated or minimized, the thickness of the separator roll can be reduced, and the process and cost can be advantageously improved.

[0149] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries, but are not limited to these.

[0150] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.

[0151] Examples of the non-aqueous organic solvent include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.

[0152] In particular, ethylene carbonate and propylene carbonate, which are cyclic carbonates among the carbonate-based organic solvents, are preferably used because they are high-viscosity organic solvents with high dielectric constants and good dissociation of lithium salts. When such cyclic carbonates are mixed with linear carbonates having low viscosity and low dielectric constants, such as dimethyl carbonate and diethyl carbonate, in an appropriate ratio, an electrolyte having high electrical conductivity can be produced, and therefore these can be used more preferably.

[0153] The metal salt may be a lithium salt, which is a substance that is easily dissolved in the non-aqueous electrolyte. For example, the anion of the lithium salt may be F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3- , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - One or more selected from the group consisting of:

[0154] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, and aluminum trichloride for the purposes of improving the life characteristics of the battery, suppressing a decrease in battery capacity, and improving the discharge capacity of the battery.

[0155] One embodiment of the present invention provides a battery module including the secondary battery as a unit cell, and a battery pack including the same. The battery module and the battery pack include the secondary battery having high capacity, high rate-limiting characteristics, and high cycle characteristics, and can be used as a power source for medium- to large-sized devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems. EXAMPLES

[0156] Below, preferred examples are presented to aid in understanding the present invention. However, these examples are intended to illustrate the present description, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present description. Naturally, such changes and modifications fall within the scope of the appended claims.

[0157] <Example> <Production of negative electrodes> Example 1: Preparation of negative electrode Manufacture of negative electrode active material layer A negative electrode active material layer composition was prepared by mixing silicon-based active material Si (average particle size (D50): 5 μm), first conductive material, second conductive material, and polyacrylamide as a binder in a weight ratio of 80:9.6:0.4:10. The negative electrode active material layer composition was prepared by adding distilled water as a solvent for forming a negative electrode slurry (solid concentration 28 wt%).

[0158] The first conductive material is plate-shaped graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm), and the second conductive material is carbon nanotubes.

[0159] The mixing method was as follows: the first conductive material, the second conductive material, the binder and the water were dispersed using a homomixer at 2500 rpm for 30 minutes, the active material was then added, and the mixture was dispersed at 2500 rpm for 30 minutes to prepare a slurry.

[0160] The negative electrode slurry was applied at 3.00 mg / cm on both sides of a copper current collector (thickness: 15 μm) as a negative electrode current collector. 2 The coated layer was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer (thickness: 23 μm).

[0161] Manufacturing of the ceramic layer A ceramic layer composition was prepared with a weight ratio of 92:8, consisting of Ce (Al2O3, d50: 300 nm) as ceramic and PVdF-HFP as organic binder. The ceramic layer composition was then added to acetone, an organic solvent, to produce the ceramic layer composition (solid concentration 18% by weight).

[0162] Then, the ceramic layer composition was coated on the negative electrode active material layer, roll pressed, and dried in a vacuum oven at 60° C. for 10 hours to form a ceramic layer (thickness: 1 μm).

[0163] A negative electrode was manufactured in the same manner as in Example 1, except that the conditions for manufacturing the negative electrode active material layer and the ceramic layer were changed as follows.

[0164] [Table 1]

[0165] Pre-lithiation process A transfer laminate consisting of PET / release layer / lithium metal was laminated on the top of the negative electrodes of Examples 1 to 5 and Comparative Examples 1 to 6, and the PET layer was removed to transfer the lithium metal onto the top of the ceramic layer.

[0166] Thereafter, the negative electrode for the lithium secondary battery was prelithiated.

[0167] <Secondary battery manufacturing> LiNi as the positive electrode active material 0.6 Co 0.2 Mn 0.2 O2 (average particle size (D50): 15 μm), carbon black (product name: SuperC65, manufacturer: Timcal) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were added in a weight ratio of 97:1.5:1.5 to N-methyl-2-pyrrolidone (NMP) as a solvent for forming a positive electrode slurry to prepare a positive electrode slurry (solid concentration 78 wt%).

[0168] The positive electrode current collector was an aluminum current collector (thickness: 12 μm) and the positive electrode slurry was applied to both sides at 537 mg / 25 cm. 2 The coated layer was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a positive electrode active material layer (thickness: 65 μm) to prepare a positive electrode (thickness of positive electrode: 77 μm, porosity: 26%).

[0169] An electrolyte was injected between the positive electrode and the negative electrode of Example 1 via a polyethylene separator, to prepare the secondary battery of Example 1.

[0170] The electrolyte was an organic solvent made by mixing fluoroethylene carbonate (FEC) and diethyl carbonate (DMC) in a volume ratio of 30:70, to which vinylene carbonate was added at 3 wt% based on the total weight of the electrolyte, and LiPF6 was added as a lithium salt at a concentration of 1M.

[0171] Except for using the negative electrodes of Examples 2 to 5 and Comparative Examples 1 to 6, secondary batteries were fabricated in the same manner as described above.

[0172] Experimental example 1. Performance evaluation by discharge C-rate In order to confirm the performance of the secondary batteries of the examples and comparative examples according to the discharge rate, a discharge rate experiment (fixed charge rate, variable discharge rate of 0.2 / 0.5 / 1.0 / 1.5 / 2.0 / 3.0 / 4.0) was carried out.

[0173] The discharge rate experiment was performed as follows: 0.33 / 0.2>0.33 / 0.33>0.33 / 0.5>0.33 / 0.33>0.33 / 1.0>0.33 / 0.33>0.33 / 1.5>0.33 / 0.33>0.33 / 2.0>0.33 / 0.33>0.33 / 3.0>0.33 / 0.33>0.33 / 4.0, and pre-lithiation was not performed separately. To confirm the ratio, the capacity for each rate was shown based on the 0.2C discharge capacity as 100%. The results are shown in Table 2 below.

[0174] [Table 2]

[0175] The ceramic layer according to the present invention does not contain a conductive material, and is composed only of an insulating material and a binder, compared to the negative electrode active material layer. Therefore, it was confirmed that the thicker the ceramic layer, the lower the rate characteristics. In addition, the higher the proportion of the binder (PVdF-HFP) in the ceramic layer, the lower the resistance because it is effective in forming a void structure in the ceramic layer. On the other hand, when the proportion of the binder is low, the ceramic material and the binder are bonded to form a layer, blocking the voids, lowering the ionic conductivity of the electrolyte and decreasing performance.

[0176] Also, as can be seen from Comparative Example 5 in Table 2, when a PAM-based binder, which is a water-based binder, is used instead of PVdF, and water (H2O), which is a water-based solvent, is used, the performance is very poor. This is because the strength of the binder becomes very high when the ceramic layer is dried, and the ceramic layer tends to become very hard. Also, because it has a chemical structure similar to that of the binder used in the silicon (Si) electrode, the ceramic layer and the negative electrode active material layer are too strongly adsorbed, resulting in very low wettability of the electrolyte.

[0177] Comparative Example 6 in Table 2 shows the results of producing a graphite electrode having the same capacity. Since the capacity of silicon is more than 10 times that of graphite, in the case of Comparative Example 6, the electrode is in a very thick coated state, and it was confirmed that the discharge rate performance was much inferior to that of Examples 1 to 5.

[0178] Experimental example 2. Electrode ignition experiment Li metal having the same size and thickness of 6.2 μm was adsorbed on the negative electrodes of the examples and comparative examples prepared above, and then left to stand for about 12 hours to completely pre-lithiate. A spark was artificially generated on the surface of the pre-lithiated negative electrodes prepared for the experiment using a plasma lighter, and the time it took for the electrodes to ignite was measured, and the results are shown in Table 3 below.

[0179] [Table 3]

[0180] As can be seen from Table 3, the negative electrodes having the ceramic layer according to the present application are all in a state of being coated with the ceramic layer, so although there are some differences in time, it was confirmed that the time until ignition is longer and the possibility of ignition is lower, resulting in high safety.

[0181] The results of Experimental Example 2 confirmed that the insulating properties are affected by the proportion of ceramic, which has the main insulating properties, and the coating thickness. Therefore, it was confirmed that Comparative Example 1, in which the insulating layer is below the thickness range of the present application, ignited at the shortest time (6 seconds) and was poor in stability.

[0182] In the case of Comparative Example 2, the thickness of the ceramic layer exceeded the range of the present application, and it was confirmed that it took more than 30 seconds to ignite. However, as can be seen from Table 2 above, it was confirmed that the discharge rate performance was very poor and that this resulted in a decrease in efficiency during pre-lithiation.

[0183] In the cases of Comparative Examples 3 and 4, the thickness of the ceramic layer satisfies the range of the present application, but the binder content is less than or exceeds the range of the present application. In these cases, the dispersibility of the ceramic itself is poor, the prelithiation rate cannot be smoothly controlled, and problems such as fires occur during the prelithiation process itself. Although the thickness of the ceramic layer satisfies the thickness range of the present application, the safety evaluation showed poor results.

[0184] Comparative Example 5 is a case where the ceramic layer was prepared using an aqueous binder and an aqueous solvent, and similarly satisfied the thickness range in the safety evaluation and had results equivalent to those of the Examples. However, as can be seen from the above-mentioned Experimental Example 1, it was confirmed that the performance evaluation was very poor.

[0185] Finally, in Comparative Example 6, a graphite-based active material was used. As described in the above Experimental Example 1, in order to achieve the same capacity, the thickness of the electrode had to be made very thick, and as a result, it was confirmed that the discharge rate performance was much inferior to that of Examples 1 to 5.

[0186] For reference, when a negative electrode not having the ceramic layer according to the present application was pre-lithiated under the same conditions and an experiment was conducted, it was confirmed that the negative electrode caught fire within 2 to 3 seconds, which is unsafe.

[0187] In conclusion, through the above examples and comparative examples, it has been confirmed that the negative electrode for a lithium secondary battery according to the present application uses a silicon-based active material and includes a ceramic layer of a specific thickness and composition on the upper part of the negative electrode active material layer, thereby stabilizing the process speed during pre-lithiation, and thus has the characteristic of being able to significantly increase the stability during the pre-lithiation process.

[0188] That is, it was confirmed that the contact points between the silicon-based anode and lithium metal can be reduced, and the charge / discharge uniformity of the silicon-based anode can be improved, thereby improving performance.

[0189] By further providing a ceramic layer on the silicon-based negative electrode active material layer, the ceramic layer formed on the separator can be eliminated or minimized, and the thickness of the separator can be reduced, resulting in excellent process and cost characteristics. [Explanation of symbols]

[0190] 10. Ceramic layer 20...Negative electrode active material layer 30 Negative electrode current collector layer

Claims

1. A negative electrode for a lithium secondary battery, comprising: a negative electrode current collector layer; a silicon-based negative electrode active material layer provided on one or both sides of the negative electrode current collector layer; and a ceramic layer provided on a surface of the silicon-based negative electrode active material layer opposite to a surface in contact with the negative electrode current collector layer, The ceramic layer comprises a ceramic layer composition or a dried product thereof; The thickness of the ceramic layer is 0.5 μm or more and 3 μm or less, The ceramic layer composition comprises a ceramic and an organic binder; The ceramic is contained in an amount of 80 parts by weight or more and 95 parts by weight or less, and the organic binder is contained in an amount of 5 parts by weight or more and 20 parts by weight or less, based on 100 parts by weight of the ceramic layer composition.

2. The ceramic is Al 2 O 3 , ZrO 2 , SiO 2 , TiO 2 , ZnO, BaTiO 3 , SrTiO 3 , CaCO 3 , CaO, CeO 2 , NiO, MgO, SnO 2 , Y 2 O 3 , Pb(Zr,Ti)O 3 (PZT), (Pb, La) (Zr, Ti) O 3 (PLZT), Pb(Mg 1/3 Nb 2/3 ) O 3 -PbTiO 3 (PMN-PT) and hafnia (HfO 2 2. The negative electrode for a lithium secondary battery according to claim 1, comprising at least one selected from the group consisting of:

3. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the organic binder is polyvinylidene fluoride (PVdF); or polyvinylidene fluoride-hexafluoropropylene (PVdF-HFP).

4. The ceramic layer composition further comprises an organic solvent; 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the organic solvent comprises at least one selected from the group consisting of N-methylpyrrolidone (NMP); dimethylformamide (DMF); acetone; and dimethylacetamide.

5. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein a surface of the ceramic layer opposite to a surface in contact with the silicon-based negative electrode active material layer is joined to lithium metal, and then the surface is left at 23° C. for 10 seconds to 2 minutes, after which the adhesive strength is 10 gf / 15 mm or more and 100 gf / 15 mm or less.

6. The silicon-based negative electrode active material layer includes a negative electrode active material layer composition, 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the negative electrode active material layer composition comprises at least one selected from the group consisting of a silicon-based active material; a negative electrode conductive material; and a negative electrode binder.

7. 7. The negative electrode for a lithium secondary battery according to claim 6, wherein the silicon-based active material comprises one or more selected from the group consisting of SiOx (x=0) and SiOx (0<x<2), and comprises 70 parts by weight or more of the SiOx (x=0) based on 100 parts by weight of the silicon-based active material.

8. The negative electrode conductive material includes a sheet conductive material and a linear conductive material, 7. The negative electrode for a lithium secondary battery according to claim 6, wherein the sheet conductive material is contained in an amount of 80 parts by weight or more and 99.9 parts by weight or less based on 100 parts by weight of the negative electrode conductive material.

9. The negative electrode for a lithium secondary battery according to claim 6 , wherein the silicon-based active material is included in an amount of 70 parts by weight or more based on 100 parts by weight of the negative electrode active material layer composition.

10. Providing a negative electrode current collector layer; applying a negative electrode active material layer composition to one or both surfaces of the negative electrode current collector layer to form a negative electrode active material layer; and applying a ceramic layer composition to a surface of the negative electrode active material layer opposite to a surface in contact with the negative electrode current collector layer to form a ceramic layer; A method for producing a negative electrode for a lithium secondary battery, comprising: The thickness of the ceramic layer is 0.5 μm or more and 3 μm or less, The ceramic layer composition includes a ceramic, an organic binder, and an organic solvent; The ceramic layer composition contains 80 parts by weight or more and 95 parts by weight or less of the ceramic, and 5 parts by weight or more and 20 parts by weight or less of the organic binder, based on 100 parts by weight of the ceramic layer composition.

11. The method for manufacturing a negative electrode for a lithium secondary battery according to claim 10, further comprising the step of drying and rolling the ceramic layer composition to remove an organic solvent from the ceramic layer composition after the ceramic layer composition is applied.

12. pre-lithiating the negative electrode having the negative electrode active material layer and the ceramic layer formed on the negative electrode current collector layer; 11. The method of claim 10, wherein the prelithiation of the negative electrode comprises a lithium electrolytic plating process; a lithium metal transfer process; a lithium metal deposition process; or a stabilized lithium metal powder (SLMP) coating process.

13. Positive electrode; The negative electrode for a lithium secondary battery according to any one of claims 1 to 9; A separator disposed between the positive electrode and the negative electrode; and Electrolyte; A lithium secondary battery comprising:

Citation Information

Patent Citations

  • Anode and secondary battery comprising same anode

    EP3916846A1

  • Transfer film, electrode plate for electrochemical element formed using the same, and lithium secondary battery

    JP2007273459A

  • Negative electrode and lithium ion secondary battery, and manufacturing method of the same

    JP2017033871A

  • Electrode and secondary battery

    JP2018037280A

  • Anode for nonaqueous electrolyte electrochemical element, manufacturing method thereof, lithium ion secondary battery and manufacturing method thereof

    JP2018142487A